Phylogenetic signal of subsets of morphological characters: a case study in the genus erythemis (anisoptera: libellulidae) (2014)
Erythemis Hagen, 1861 shows a considerable variation in genitalic characters, body coloration and wing venation. Since it is known that these traits are affected by different kinds of selection that probably blur their phylogenetic signal, we chose the genus Erythemis as a model taxon to analyze and compare the phylogenetic signal of these and other morphologic characters. A cladistic analysis was performed using ten species of the genus plus another seventeen species of Libellulidae as outgroup. Characters were defined following standard criteria and were managed using the software DELTA. Tree search was performed with the software NONA. Partitioned and combined analyses were conducted. Character tracking of characters with ri=100 was used to identify synapomorphies. In agreement with the literature, color characters provided strong phylogenetic signal, meanwhile, genitalia characters offered no synapomorphies. We did not find any character that could support the monophyly of Erythemis. The only clade that has strong support from the morphologic set of characters is (E. vesiculosa, (E. simplicicollis, E. collocata)). Contrary to the results found in other Odonata, wing characters offered synapomorphies for some Erythemis clades.